Cyano-functionalized hypercrosslinked polystyrene resin as well as preparation method and application thereof

Through the use of cyanoma -based ultra -high -cross -cross -colly polystyrene resin in the treatment of fire -explosive wastewater, the problem of poor adsorption effect on the existing adsorption agent has a poor effect on RDX adsorption, and the efficient and economical RDX removal effect is achieved.

CN119350665AActive Publication Date: 2025-01-24LANZHOU UNIV +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411467275.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24
Estimated Expiration
2044-10-21

AI Technical Summary

Technical Problem

The existing adsorbents have poor adsorption effect on RDX, resulting in the need to use a large amount of adsorbent in the pyrogenic wastewater to achieve the expected RDX removal effect.

Method used

By reacting the chloride -based polystyrene resin with cyanomytic aroma, the alkylated response is performed under the action of catalysts, the cyanomye functional polystyrene resin is obtained, and an external cross -linking agent is introduced through the secondary cross -linking. Cyanomyalized ultra -high cross -linked polystyel resin.

Benefits of technology

Through electrostatic interactions and weak hydrogen bonds, the resin significantly improves the adsorption effect on RDX, reduces the amount of adsorbent used, and maintains a high specific surface area and rapid adsorption and removal effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350665A_ABST
    Figure CN119350665A_ABST
Patent Text Reader

Abstract

The invention provides cyano-functionalized hypercrosslinked polystyrene resin as well as a preparation method and application thereof, and belongs to the technical field of adsorption resin for treating explosive and powder wastewater. According to the method, chloromethylated polystyrene resin is used as a raw material, two Friedel-Crafts alkylation reactions are used as core reactions to successfully prepare the functionalized secondary cross-linked resin, and the method comprises the following steps: in the previous step, the resin is subjected to internal cross-linking and cyano functional modification; in the next step, crosslinking is carried out under the action of an external crosslinking agent, and further crosslinking is carried out in the resin. The secondary cross-linked resin prepared by the invention not only realizes cyano functionalization, but also keeps a relatively high specific surface area and forms a graded pore structure mainly comprising micropores. The cyano-functionalized hypercrosslinked polystyrene resin can selectively adsorb RDX in a solution through electrostatic interaction and hydrogen bonds, shows relatively high adsorption capacity and rapid adsorption and removal effects, and has a wide application prospect in treatment of explosive and powder wastewater containing RDX.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption resins for treating explosive wastewater, and in particular to a cyano-functionalized ultra-high cross-linked polystyrene resin and a preparation method and application thereof. Background Art

[0002] RDX is a high-energy explosive used in a variety of military and other applications such as nuclear devices, rocket propellants, plastic explosives, rocket fuel, detonators, construction, quarrying and mining. The inselective disposal of RDX wastes from production sites, blast sites and unexploded ordnance has led to severe environmental contamination of soil and water bodies. Adsorption is simple and effective and is one of the most effective technologies for the removal of RDX.

[0003] Ultra-high cross-linked polymers have a high BET surface area (S BET ), good porosity and diverse functionality, and are considered to be good adsorbents for organic pollutants. In recent years, new microporous organic polymers prepared using ultra-high cross-linking technology have shown excellent performance in gas capture and storage, removal of aromatic organic matter and recovery of heavy metals. For example, HPVE-04, HPVE-13 and HPVE-40 have been shown to effectively adsorb phenol, p-nitrophenol and rhodamine B, respectively.

[0004] Macroporous low cross-linked chloromethylated polystyrene resin is a common raw material for producing ultra-high cross-linked polymers. It is obtained through the traditional Friedel-Crafts reaction. Under the action of the catalyst Lewis acid, the side chain -CH 2 The Cl group acts as an electrophilic reagent and can undergo electrophilic substitution reaction with adjacent phenyl groups. A large number of methylene groups act as cross-linking bridges to connect adjacent phenyl groups, making S BET Rapid increase and formation of microporous structure. General ultra-high cross-linked resins have good adsorption effects on a variety of organic matter, but the organic wastewater generated in the RDX production process usually contains ethyl acetate, acetone and a small amount of RDX. Traditional ultra-high cross-linked resins tend to effectively adsorb organic matter with high content of ethyl acetate and acetone, but have poor adsorption effect on relatively small content of RDX, resulting in the need for a large amount of adsorbent to achieve the expected RDX removal effect. Therefore, it is of great practical significance to develop a new functional ultra-high cross-linked resin that selectively adsorbs RDX. Summary of the invention

[0005] The purpose of the present invention is to provide a cyano functionalized ultra-high cross-linked polystyrene resin and a preparation method and application thereof, so as to solve the technical problem that the existing adsorbent has a poor adsorption effect on RDX.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a method for preparing a cyano-functionalized ultra-high cross-linked polystyrene resin, comprising the following steps:

[0008] 1) adding a chloromethylated polystyrene resin into an organic solvent containing aromatic nitrile to swell the resin, and then performing an alkylation reaction under the action of a catalyst to obtain a cyano-functionalized polystyrene resin;

[0009] 2) swelling the cyano-functionalized polystyrene resin in an organic solvent, and then adding a catalyst to obtain a mixture;

[0010] 3) When the temperature of the mixture reaches the target temperature, an organic solvent containing an external cross-linking agent is added to the mixture to carry out a cross-linking reaction, thereby obtaining a cyano-functionalized ultra-high cross-linked polystyrene resin.

[0011] Further, the aromatic nitrile is an aromatic compound containing a cyano group;

[0012] In step 1), the mass ratio of the aromatic nitrile to the chloromethylated polystyrene resin is 1:10-20, the volume mass ratio of the organic solvent to the chloromethylated polystyrene resin is 10-40 mL:1 g; and the mass ratio of the catalyst to the chloromethylated polystyrene resin is 1:3-4.

[0013] Furthermore, in the step 1), the swelling time is 8 to 10 hours, the temperature of the alkylation reaction is 45 to 85° C., and the alkylation reaction time is 8 to 18 hours.

[0014] Furthermore, the external cross-linking agent comprises one or more of dimethylformal, p-dichlorobenzyl and biphenyl dichlorobenzyl.

[0015] Furthermore, in the step 2), the volume mass ratio of the organic solvent to the cyano functionalized polystyrene resin is 10-20 mL:1 g; and the mass ratio of the catalyst to the cyano functionalized polystyrene resin is 1:1-2.

[0016] Furthermore, in step 3), the target temperature is 45 to 85° C., and the cross-linking reaction time is 8 to 18 hours.

[0017] Furthermore, the mass ratio of the external cross-linking agent to the cyano-functionalized polystyrene resin is 0.3 to 1.5:1;

[0018] In the step 3), the mass volume ratio of the external cross-linking agent to the organic solvent is 0.3-1.5 g: 10-20 mL.

[0019] Furthermore, in step 1) and step 2), the catalyst independently comprises one or more of anhydrous ferric chloride, anhydrous aluminum chloride, anhydrous zinc chloride and anhydrous titanium chloride;

[0020] In the steps 1), 2) and 3), the organic solvent independently comprises one or more of dichloromethane, 1,2-dichloroethane, nitromethane, nitrobenzene and carbon disulfide.

[0021] The invention provides a cyano functionalized ultra-high cross-linked polystyrene resin.

[0022] The invention also provides an application of cyano functionalized ultra-high cross-linked polystyrene resin as an adsorbent in explosive wastewater.

[0023] Beneficial effects of the present invention:

[0024] 1. The present invention selects cheap and readily available chloromethylated polystyrene resin as raw material, and realizes the synthesis of ultra-high cross-linked polymers through mature Friedel-Crafts alkylation reaction. The whole process is simple to operate, and the required reagents can be directly purchased, which has economic benefits and direct commercial application value.

[0025] 2. The present invention utilizes the electrostatic interaction and weak hydrogen bond between cyano and RDX to innovatively prepare cyano-functionalized ultra-high cross-linked polystyrene adsorption resin, thereby improving the adsorption effect of RDX in explosive wastewater.

[0026] 3. The present invention introduces an external cross-linking agent through secondary cross-linking, and makes the internal cross-linking of the resin more thorough, further increasing the specific surface area of ​​the resin, compensating for the reduction in specific surface area caused by functionalization, and improving the adsorption effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a flow chart for preparing the cyano-functionalized ultra-high cross-linked polystyrene adsorption resin;

[0028] Figure 2 N is the N of various resins involved in the present invention. 2 Adsorption-desorption isotherms and pore size distribution diagrams;

[0029] Figure 3 It is the Fourier transform infrared spectra of various resins involved in the present invention;

[0030] Figure 4 The adsorption rate of the secondary cross-linked resin (biphenyl dichlorobenzyl) to RDX in the present invention changes with time and the kinetic fitting curve;

[0031] Figure 5 The curve of the adsorption rate of the secondary cross-linked resin (benzyl dichloride) to RDX over time and the kinetic fitting curve in the present invention;

[0032] Figure 6It is the time variation curve and the kinetic fitting curve of the adsorption rate of RDX by the secondary cross-linking resin (dimethanol formal) in the present invention. DETAILED DESCRIPTION

[0033] The present invention provides a method for preparing a cyano-functionalized ultra-high cross-linked polystyrene resin, comprising the following steps:

[0034] 1) adding a chloromethylated polystyrene resin into an organic solvent containing aromatic nitrile to swell the resin, and then performing an alkylation reaction under the action of a catalyst to obtain a cyano-functionalized polystyrene resin;

[0035] 2) swelling the cyano-functionalized polystyrene resin in an organic solvent, and then adding a catalyst to obtain a mixture;

[0036] 3) When the temperature of the mixture reaches the target temperature, an organic solvent containing an external cross-linking agent is added to the mixture to carry out a cross-linking reaction, thereby obtaining a cyano-functionalized ultra-high cross-linked polystyrene resin.

[0037] In the present invention, the chloromethylated polystyrene resin is passed through a 20-40 mesh sieve, preferably a 30 mesh sieve, before swelling.

[0038] In the present invention, the aromatic nitrile is an aromatic compound containing a cyano group, preferably one or more of benzonitrile, terephthalonitrile, phthalonitrile, isophthalonitrile and benzyl nitrile, more preferably one or more of benzonitrile, terephthalonitrile and phthalonitrile.

[0039] In the present invention, in step 1), the mass ratio of the aromatic nitrile to the chloromethylated polystyrene resin is 1:10-20, preferably 1:12-18, and more preferably 1:15; the volume mass ratio of the organic solvent to the chloromethylated polystyrene resin is 10-40 mL:1 g, preferably 15-35 mL:1 g, and more preferably 20-30 mL:1 g; the mass ratio of the catalyst to the chloromethylated polystyrene resin is 1:3-4, and more preferably 1:3.5.

[0040] In the present invention, in the step 1), the swelling time is 8 to 10 hours, preferably 9 hours; the temperature of the alkylation reaction is 45 to 85°C, preferably 50 to 80°C, and more preferably 60 to 70°C; the alkylation reaction time is 8 to 18 hours, preferably 10 to 15 hours, and more preferably 12 to 14 hours.

[0041] In the present invention, the external crosslinking agent comprises one or more of dimethylformal, p-dichlorobenzyl and biphenyl dichlorobenzyl, preferably biphenyl dichlorobenzyl.

[0042] In the present invention, in the step 2), the volume mass ratio of the organic solvent to the cyano-functionalized polystyrene resin is 10-20 mL:1 g, preferably 12-18 mL:1 g, and more preferably 15 mL:1 g; the mass ratio of the catalyst to the cyano-functionalized polystyrene resin is 1:1-2, preferably 1:1.5.

[0043] In the present invention, in step 3), the target temperature is 45 to 85°C, preferably 50 to 80°C, and more preferably 60 to 70°C; the cross-linking reaction time is 8 to 18 hours, preferably 10 to 15 hours, and more preferably 12 to 13 hours.

[0044] In the present invention, the mass ratio of the external cross-linking agent to the cyano-functionalized polystyrene resin is 0.3 to 1.5:1, preferably 0.5 to 1.2:1, and more preferably 0.8 to 1.0:1;

[0045] In the step 3), the mass volume ratio of the external cross-linking agent to the organic solvent is 0.3-1.5 g:10-20 mL, preferably 0.5-1.2 g:12-18 mL, and more preferably 0.8-1.0 g:14-16 mL.

[0046] In the present invention, in step 1) and step 2), the catalyst independently comprises one or more of anhydrous ferric chloride, anhydrous aluminum chloride, anhydrous zinc chloride and anhydrous titanium chloride, preferably anhydrous ferric chloride;

[0047] In the steps 1), 2) and 3), the organic solvent independently comprises one or more of dichloromethane, 1,2-dichloroethane, nitromethane, nitrobenzene and carbon disulfide, preferably 1,2-dichloroethane.

[0048] In the present invention, in the step 1), after the alkylation reaction, the obtained product is washed several times with anhydrous ethanol and 1% hydrochloric acid, and then the resin is extracted with a Soxhlet extractor at 80-120° C. until it is completely clean, and then vacuum dried at 60-80° C. for 12-24 hours to obtain a cyano-functionalized polystyrene resin.

[0049] In the present invention, in the step 3), after the cross-linking reaction, the obtained product is washed several times with anhydrous ethanol and 1% hydrochloric acid, and then the resin is extracted by a Soxhlet extractor at 80-120° C. until it is completely clean, and then vacuum dried at 60-80° C. for 12-24 hours to obtain a cyano-functionalized ultra-high cross-linked polystyrene resin.

[0050] In the present invention, the solvent in the Soxhlet extractor comprises one or more of methanol, ethanol, acetone and 1,2-dichloroethane, preferably methanol.

[0051] The invention provides a cyano functionalized ultra-high cross-linked polystyrene resin.

[0052] The invention also provides an application of cyano functionalized ultra-high cross-linked polystyrene resin as an adsorbent in explosive wastewater.

[0053] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0054] Example 1

[0055] 1) Functionalization and internal cross-linking:

[0056] First, chlorinated polystyrene resin was passed through a 30-mesh screen. Then, 0.75 g of benzonitrile was dissolved in 150 mL of 1,2-dichloroethane at room temperature, and then 15 g of chlorinated polystyrene resin was added to swell in the mixed solution for 10 h. Under mechanical stirring, 4.0 g of anhydrous FeCl 3 Rapidly add it into the reaction mixture, and raise the temperature of the reaction mixture to 85°C and keep it warm for 8 hours. Filter the obtained resin particles, wash them several times with anhydrous ethanol and 1% hydrochloric acid, and then use a Soxhlet extractor to extract the resin at 120°C until it is completely clean, and vacuum dry it at 60°C for 24 hours to obtain a cyano-functionalized polystyrene resin, referred to as cyano resin.

[0057] 2) external cross-linking and further internal cross-linking;

[0058] The above 2g cyano resin was added to 20mL 1,2-dichloroethane prepared in advance and swelled for 10h. 1.6g anhydrous FeCl was added at room temperature. 3 , stir mechanically to completely dissolve, wait until the temperature of the reaction mixture rises to 85°C, quickly pour 20mL of 1,2-dichloroethane solution containing 2.512g of biphenyl dichlorobenzyl into the three-necked flask containing the reactants, and reflux for 8h. Filter the obtained resin particles, wash them several times with anhydrous ethanol and 1% hydrochloric acid, and then use a Soxhlet extractor to extract the resin at 120°C until it is completely clean, and vacuum dry at 60°C for 24h to obtain a secondary cross-linked cyano-functionalized ultra-high cross-linked polystyrene resin (external cross-linking agent: biphenyl dichlorobenzyl), referred to as secondary cross-linked resin (biphenyl dichlorobenzyl).

[0059] The BET specific surface area S of this resin BET 970.23m 2 / g, microporosity S micro / S BET The BJH pore volume V BJH 0.35m 3 / g, average pore size D avg It is 5.77nm.

[0060] Adsorption kinetics experiment:

[0061] A series of RDX solutions with a concentration of 20 mg / L and a pH of 7 were accurately prepared using a volumetric flask. The amount of secondary cross-linking resin (diphenylbenzyl chloride) was 2 g / L. The solutions were placed in a constant temperature shaker at a temperature of 30°C and a rotation speed of 180 r / min for adsorption reaction for 3 hours. After that, they were filtered through a syringe with a 0.22 μm filter head. The sample solutions collected at different times were measured using high performance liquid chromatography. The measured peak height and peak area were substituted into the regression equation to obtain the RDX concentration (mg / L) in the sample solution at that time.

[0062] like Figure 4 As shown in the figure, the pseudo-first-order kinetic constant k of the adsorption experiment is 1 0.1040min –1 , the adsorption capacity q was calculated using the pseudo-first-order kinetic model cal,1 is 7.96 mg / g, and the correlation coefficient R 1 2 The pseudo-second-order kinetic constant k is 0.88. 2 The adsorption capacity q was calculated by pseudo-second-order kinetic model. cal,2 is 8.60 mg / g, and the correlation coefficient R 2 2 is 0.95. Obviously, the pseudo-second-order kinetic model has a better fitting degree.

[0063] Example 2

[0064] 1) Functionalization and internal cross-linking:

[0065] First, chlorinated polystyrene resin was passed through a 30-mesh screen. Then, 1.5 g of benzonitrile was dissolved in 150 mL of 1,2-dichloroethane at room temperature, and then 15 g of chlorinated polystyrene resin was added to swell in the mixed solution for 10 h. Under mechanical stirring, 4.0 g of anhydrous FeCl 3 Rapidly add it into the reaction mixture, and raise the temperature of the reaction mixture to 85°C and keep it warm for 8 hours. Filter the obtained resin particles, wash them several times with anhydrous ethanol and 1% hydrochloric acid, and then use a Soxhlet extractor to extract the resin at 120°C until it is completely clean, and vacuum dry it at 60°C for 24 hours to obtain a cyano-functionalized polystyrene resin, referred to as cyano resin.

[0066] 2) External cross-linking and further internal cross-linking:

[0067] The above 2g cyano resin was added to 20mL 1,2-dichloroethane prepared in advance and swelled for 10h. 1.6g anhydrous FeCl was added at room temperature. 3, stir mechanically to completely dissolve, wait until the temperature of the reaction mixture rises to 85°C, quickly pour 20mL 1,2-dichloroethane solution containing 1.75g ​​of p-dichlorobenzyl into the three-necked flask containing the reactants, and reflux for 8h. Filter the obtained resin particles, wash them several times with anhydrous ethanol and 1% hydrochloric acid, and then use a Soxhlet extractor to extract the resin at 120°C until it is completely clean, and vacuum dry at 60°C for 24h to obtain a secondary cross-linked cyano-functionalized ultra-high cross-linked polystyrene resin (external cross-linking agent: p-dichlorobenzyl), referred to as secondary cross-linked resin (p-dichlorobenzyl).

[0068] The BET specific surface area S of this resin BET 850.09m 2 / g, microporosity S micro / S BET The BJH pore volume V BJH 0.27m 3 / g, average pore size D avg It is 4.97nm.

[0069] Adsorption kinetics experiment:

[0070] A series of RDX solutions with a concentration of 20 mg / L and a pH of 7 were accurately prepared using a volumetric flask. The amount of secondary cross-linking resin (benzyl dichloride) was 2 g / L. The solutions were placed in a constant temperature shaker at a temperature of 30°C and a rotation speed of 180 r / min for adsorption reaction for 3 hours. After that, they were filtered through a syringe with a 0.22 μm filter head. The sample solutions collected at different times were measured using high performance liquid chromatography. The measured peak height and peak area were substituted into the regression equation to obtain the RDX concentration (mg / L) in the sample solution at that time.

[0071] like Figure 5 As shown in the figure, the pseudo-first-order kinetic constant k of the adsorption experiment is 1 0.0898min –1 , the adsorption capacity q was calculated using the pseudo-first-order kinetic model cal,1 is 7.52 mg / g, and the correlation coefficient R 1 2 is 0.85; the pseudo-second-order kinetic constant k 2 The adsorption capacity q was calculated by pseudo-second-order kinetic model. cal,2 is 8.13 mg / g, and the correlation coefficient R 2 2 is 0.93. Obviously, the pseudo-second-order kinetic model has a better fitting degree.

[0072] Example 3

[0073] 1) Functionalization and internal cross-linking:

[0074] First, chlorinated polystyrene resin was passed through a 30-mesh screen. Then, 2.25 g of benzonitrile was dissolved in 150 mL of 1,2-dichloroethane at room temperature, and then 15 g of chlorinated polystyrene resin was added to swell in the mixed solution for 10 h. Under mechanical stirring, 4.0 g of anhydrous FeCl 3 Rapidly add it into the reaction mixture, and raise the temperature of the reaction mixture to 85°C and keep it warm for 8 hours. Filter the obtained resin particles, wash them several times with anhydrous ethanol and 1% hydrochloric acid, and then use a Soxhlet extractor to extract the resin at 120°C until it is completely clean, and vacuum dry it at 60°C for 24 hours to obtain a cyano-functionalized polystyrene resin, referred to as cyano resin.

[0075] 2) External cross-linking and further internal cross-linking:

[0076] The above 2g cyano resin was added to 20mL 1,2-dichloroethane prepared in advance and swelled for 10h. 1.6g anhydrous FeCl was added at room temperature. 3 , stir mechanically to completely dissolve it, wait until the temperature of the reaction mixture rises to 85°C, quickly pour 20mL of 1,2-dichloroethane solution containing 0.762g of dimethylformal into the three-necked flask containing the reactants, and reflux for 8h. Filter the obtained resin particles, wash them several times with anhydrous ethanol and 1% hydrochloric acid, and then use a Soxhlet extractor to extract the resin at 120°C until it is completely clean, and vacuum dry it at 60°C for 24h to obtain a secondary cross-linked cyano-functionalized ultra-high cross-linked polystyrene resin (external cross-linking agent: dimethylformal), referred to as secondary cross-linked resin (dimethanolformal).

[0077] The BET specific surface area S of this resin BET 891.06m 2 / g, microporosity S micro / S BET The BJH pore volume V BJH 0.31m 3 / g, average pore size D avg It is 5.73nm.

[0078] Adsorption kinetics experiment:

[0079] A series of RDX solutions with a concentration of 20 mg / L and a pH of 7 were accurately prepared using a volumetric flask. The amount of secondary cross-linking resin (dimethanol formal) was 2 g / L. The solutions were placed in a constant temperature shaker at a temperature of 30°C and a rotation speed of 180 r / min for adsorption reaction for 3 hours. After that, they were filtered through a syringe with a 0.22 μm filter head. The sample solutions collected at different times were measured using high performance liquid chromatography, and the measured peak height and peak area were substituted into the regression equation to obtain the RDX concentration (mg / L) in the sample solution at that time.

[0080] like Figure 6 As shown in the figure, the pseudo-first-order kinetic constant k of the adsorption experiment is 1 0.1284min –1 , the adsorption capacity q was calculated using the pseudo-first-order kinetic model cal,1 is 8.61 mg / g, and the correlation coefficient R 1 2 The pseudo-second-order kinetic constant k 2 The adsorption capacity q was calculated by pseudo-second-order kinetic model. cal,2 is 9.34 mg / g, and the correlation coefficient R 2 2 is 0.99. Obviously, the pseudo-second-order kinetic model has a better fitting degree.

[0081] Comparative Example 1

[0082] First, 15 g of chloromethylated polystyrene resin was sieved through a 30-mesh screen. Then 15 g of chloromethylated polystyrene resin was swelled in 150 mL of 1,2-dichloroethane for 10 h. Under mechanical stirring, 4.0 g of anhydrous FeCl 3 Rapidly add it to the above mixture, raise the reaction temperature to 85°C, and keep it warm for 8 hours. Filter the obtained resin particles, wash them several times with anhydrous ethanol and 1% hydrochloric acid, and then use a Soxhlet extractor to extract the resin at 120°C until it is completely clean, and vacuum dry it at 60°C for 24 hours to obtain a non-functionalized ultra-high cross-linked polystyrene resin.

[0083] Verification of the structure of cyano-functionalized ultra-high cross-linked polystyrene adsorption resin

[0084] The present invention describes the physical and chemical structures of the six resins involved by two characterization methods:

[0085] 1. BET specific surface area and BJH pore size distribution

[0086] like Figure 2 As shown, the S of the raw material chloromethylated polystyrene resin BET 31.55m 2 / g( Figure 2 a), S of the ultra-high cross-linked resin obtained by direct cross-linking without adding a modifier (Comparative Example 1) BET 1084.11m 2 / g( Figure 2 b), indicating that the use of ultra-high cross-linking technology can indeed greatly increase the S BET . Cyanoresin S BET 803.59m 2 / g( Figure 2 c), which is lower than that of the ultra-high cross-linked resin, but still maintains a high value. This is because the introduction of benzonitrile and part of -CH2 The S of the three secondary cross-linked resins obtained using different external cross-linking agents were BET There was a rebound, especially for the secondary cross-linking resin (biphenyl dichlorobenzyl), S BET Compared with cyano resin, it increased by 20.7%, indicating that the external cross-linking agent can increase the S BET The pore volume and pore size of the ultra-high cross-linked resin increased and decreased significantly compared with the chloromethylated polystyrene resin, and the introduction of the modifier did not change this trend.

[0087] 2. Fourier transform infrared spectroscopy (FT-IR)

[0088] like Figure 3 As shown, at 1267cm –1 -CH 2 The Cl stretching vibration absorption peak gradually weakens with the increase of cross-linking times, indicating that the degree of cross-linking increases. –1 The absorption peak at 100° is related to the methylene bridge (-CH 2 -). It is worth noting that at 2335cm –1 The characteristic absorption peak at 3018cm is related to the C≡N stretching vibration, indicating that the resin was successfully modified. –1 The peak at the C-H bond stretching vibration of the benzene ring is 0.1777 W, and the secondary cross-linked resin (biphenyl dichlorobenzyl) shows the highest strength, which proves the successful introduction of the external cross-linking agent.

[0089] Through the above examples, a series of cyano-functionalized ultra-high cross-linked polystyrene adsorption resins with high specific surface area and adsorption capacity were prepared. Table 1 is a comparison of the specific surface area, actual adsorption amount and calculated adsorption amount of each example.

[0090] Table 1 Comparison of specific surface area of ​​each example and actual adsorption amount and calculated adsorption amount

[0091]

[0092]

[0093] Experimental example

[0094] Application of cyano-functionalized ultra-high cross-linked polystyrene adsorption resin

[0095] The adsorption performance of the cyano-functionalized ultra-high cross-linked polystyrene adsorption resin obtained in the example to RDX was tested, and the specific steps are as follows:

[0096] 1) Preparation of RDX standard solution: Accurately weigh a certain amount of RDX (analytical grade), dissolve it in a small amount of acetone to form a saturated solution, transfer it quantitatively to a volumetric flask with deionized water, and make up to volume. This solution is the RDX standard stock solution. Before use, dilute it with deionized water to a 60 mg / L RDX standard solution.

[0097] 2) Drawing of the RDX solution concentration standard curve: Take 5-7 volumetric flasks and dilute the RDX standard solution with deionized water to form a series of RDX standard concentration solutions ranging from 0.0 mg / L to 60.0 mg / L. Adjust the high performance liquid chromatograph to the optimal measurement state and set the instrument parameters (measurement wavelength: 210 nm; chromatographic column: 250 mm × 4.6 mm × 5 μm, C 18 ; Column temperature: 25℃; Mobile phase: methanol: water = 60:40 (V / V); Mobile phase flow rate: 1.0mL / min), inject 10μL, and measure the peak height or peak area of ​​each concentration of the standard solution series. Draw a standard curve with the measured peak height or peak area against the corresponding RDX concentration (mg / L) and calculate the regression equation, and its correlation coefficient should be ≥0.999.

[0098] 3) Adsorption kinetics experiment: Use a volumetric flask to accurately prepare a series of RDX solutions with a concentration of 10-60 mg / L and a pH of 2-11. The amount of secondary cross-linking resin is 2-4 g / L. Place it in a constant temperature shaker at a temperature of 20-40 ° C and a rotation speed of 120-220 r / min for adsorption reaction for 3-6 hours, then filter it through a syringe with a 0.20-0.24 μm filter head. Use high performance liquid chromatography to measure the sample solutions collected at different times, and substitute the measured peak height and peak area into the regression equation to obtain the RDX concentration (mg / L) in the sample solution at that time. The experimental results are as follows Figures 4 to 6 .

[0099] It can be seen from the above embodiments that the present invention provides a cyano-functionalized ultra-high cross-linked polystyrene resin and its preparation method and application. The secondary cross-linked resin prepared by the present invention not only realizes cyano functionalization, but also maintains a high specific surface area and forms a hierarchical pore structure dominated by micropores. The cyano-functionalized ultra-high cross-linked polystyrene resin can selectively adsorb RDX in the solution through electrostatic interaction and hydrogen bonding, showing a high adsorption capacity and rapid adsorption and removal effect, and has broad application prospects for treating RDX-containing explosive wastewater.

[0100] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a cyano-functionalized ultra-high cross-linked polystyrene resin, characterized in that: The following steps are involved: 1) adding a chloromethylated polystyrene resin into an organic solvent containing aromatic nitrile to swell the resin, and then performing an alkylation reaction under the action of a catalyst to obtain a cyano-functionalized polystyrene resin; 2) swelling the cyano-functionalized polystyrene resin in an organic solvent, and then adding a catalyst to obtain a mixture; 3) When the temperature of the mixture reaches the target temperature, an organic solvent containing an external cross-linking agent is added to the mixture to carry out a cross-linking reaction, thereby obtaining a cyano-functionalized ultra-high cross-linked polystyrene resin.

2. The method for preparing a cyano-functionalized ultra-high cross-linked polystyrene resin according to claim 1, characterized in that: The aromatic nitrile is an aromatic compound containing a cyano group; In step 1), the mass ratio of the aromatic nitrile to the chloromethylated polystyrene resin is 1:10-20, the volume mass ratio of the organic solvent to the chloromethylated polystyrene resin is 10-40 mL:1 g; and the mass ratio of the catalyst to the chloromethylated polystyrene resin is 1:3-4.

3. The method for preparing a cyano-functionalized ultra-high cross-linked polystyrene resin according to claim 1 or 2, characterized in that: In the step 1), the swelling time is 8 to 10 hours, the temperature of the alkylation reaction is 45 to 85° C., and the alkylation reaction time is 8 to 18 hours.

4. The method for preparing the cyano functionalized ultra-high cross-linked polystyrene resin according to claim 3, characterized in that: The external cross-linking agent comprises one or more of dimethylformal, p-dichlorobenzyl and biphenyl dichlorobenzyl.

5. The method for preparing a cyano-functionalized ultra-high cross-linked polystyrene resin according to claim 1, 2 or 4, characterized in that: In the step 2), the volume mass ratio of the organic solvent to the cyano functionalized polystyrene resin is 10-20 mL:1 g; and the mass ratio of the catalyst to the cyano functionalized polystyrene resin is 1:1-2.

6. The method for preparing the cyano functionalized ultra-high cross-linked polystyrene resin according to claim 5, characterized in that: In the step 3), the target temperature is 45 to 85° C., and the cross-linking reaction time is 8 to 18 hours.

7. The method for preparing a cyano-functionalized ultra-high cross-linked polystyrene resin according to claim 4 or 6, characterized in that: The mass ratio of the external cross-linking agent to the cyano-functionalized polystyrene resin is 0.3 to 1.5:1; In the step 3), the mass volume ratio of the external cross-linking agent to the organic solvent is 0.3-1.5 g: 10-20 mL.

8. The method for preparing the cyano functionalized ultra-high cross-linked polystyrene resin according to claim 7, characterized in that: In the step 1) and the step 2), the catalyst independently comprises one or more of anhydrous ferric chloride, anhydrous aluminum chloride, anhydrous zinc chloride and anhydrous titanium chloride; In the steps 1), 2) and 3), the organic solvent independently comprises one or more of dichloromethane, 1,2-dichloroethane, nitromethane, nitrobenzene and carbon disulfide.

9. The cyano-functionalized ultra-high cross-linked polystyrene resin prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the cyano functionalized ultra-high cross-linked polystyrene resin according to claim 9 as an adsorbent in explosive wastewater.

Citation Information

Patent Citations

  • Substituted arylpyrazoles

    CN101600696A

  • Preparation method of ultra-high crosslinking type adsorptive resin modified by N-methyl acetamido

    CN102350316A

  • Selective hydrogenating method for polar polymer

    CN107722147A

  • Amidoxime-based super-crosslinked microporous resin efficient uranium adsorbent and preparation method thereof

    CN111437798A

  • Adsorption resin with porous structure and preparation method thereof

    CN118580405A